GROWTH OPTIONS, DIVIDEND PAYOUT RATIOS AND PORTFOLIO STOCK RETURNS: EVIDENCE FROM PAKISTAN STOCK EXCHANGE - Qurat-ul-ain; Tahira Ajmal; Aisha Jamil; Kanwal Iqbal; Ammara Sarwar (International Journal of Contemporary Issues in Social Sciences, 2023)
The study analyzes the future stock returns affected by different sets of criteria in an emerging market of Pakistan and importance of momentum strategy to predict future stock returns. Trading strategies that buy past winners and sell past losers realize significant abnormal returns over the period of January, 2009 to December, 2016. We construct 15 portfolios based on mentioned criteria. Results show that high dividend paying companies in short & medium term follow the momentum strategies while in long run might be followed contrarian strategy. Similarly, high medium and low paying companies in long run do not follow momentum but in short and medium run they follow momentum. As pointed out by (George li, 2016) that on future stocks and price momentum, dividend payout ratio has a significant impact. Interestingly for the medium-run all securities of the different sets of criteria have a positive and significant effect, which means they follow momentum in future. The study is helpful for funds managers who are responsible for organizing practical plans on the behalf of the financiers. The findings of this study are helpful to them in measuring the performance of the stock market and it is also supportive in making buying and selling decisions.